Proporção de rotavírus, norovírus e Cryptosporidium ssp. em crianças com diarreia aguda atendidas no Hospital de Urgências de Sergipe - Vicente, Ana Paula Constantino do Amaral (2017)
Acute diarrhea is one of the most common infectious diseases and still one of the leading causes of morbidity and mortality in the pediatric world, a global public health problem. Several efforts have been made over the years to reduce infant mortality, despite the commitment of diarrhea still occupy a significant space of malnutrition in children under 5 years. A wide spectrum of enteric pathogens can cause acute childhood diarrhea, among which we can mention Rotavirus, Norovirus and Cryptosporidium spp. Rotavirus is one of the most important. Currently two live attenuated live Rotavirus vaccines have been licensed and are available globally: a human monovalent strain (RV1) (Rotarix®, GlaxoSmithKline Biologicals) and a pentavalent bovine-human rearrangement (RV5) (Rotateq®). Brazil was one of the first countries to integrate the vaccine into its national immunization program (2006), and it was possible to observe significant improvements in reducing infant mortality and hospitalizations for diarrheal diseases in children from Rotavirus. However, diarrhea continues to be a serious health problem, and can be avoidable and treatable. Several etiological agents may be related to these intestinal infections and deserve to be investigated. The objective of this study was to verify the presence of the three etiological agents Cryptosporidium spp., Rotavirus and Norovirus, associated with diarrhea in children aged 0 to 11 years old, attended at Sergipe Emergency Hospital (HUSE). The samples were tested by Elisa for Cryptosporidium spp and Rotavirus for fecal antigen detection and reverse transcription polymerase chain reaction (RT-PCR) for Norovirus detection. A total of 92 diarrheic stool specimens were analyzed, of which 62% were positive for one of the pathogens studied, 49% positive for Norovirus, 10% for Rotavirus, 4% for Crysptoporidium spp and 37% of diarrheal samples were not positive for any enteropathogen studied. Norovirus was the main cause of childhood diarrhea in the period studied, with predominance (98%) of the GII genotype. The most affected age group were children younger than 24 months. Infections have shown similar symptoms. Complementary studies are needed to discover other etiological agents involved in gastroenteritis in the State of Sergipe, since a significant number of children with diarrhea did not present positivity to any of the pathogens studied.